Intimate negotiations - Night, Nicki (Harlequin desire, 2021)
"Zoe Baldwin escaped her poverty-stricken youth to become a successful investment banking dynamo at the top of her game. But a forbidden office affair with her new boss, Ethan Blackwell, could ruin both their careers. And an unexpected pregnancy makes the stakes even higher. Will she and her billionaire playboy come to new terms when business becomes too personal? "--